(untitled) (Research and Practice of Educational Chemistry, 2024)
Chemistry education often faces challenges in engaging high school students due to the complexity of the subject matter. This study proposes a context-based approach, utilizing the rich cultural heritage of Cirebon Batik, to enhance students’ understanding of chemistry concepts. By integrating local wisdom into the curriculum, the study aims to bridge the gap between abstract scientific knowledge and real-world applications. The research employs the Model of Educational Reconstruction (MER) to analyze the scientific content within batik-making and implement didactic reduction strategies to simplify complex concepts. The study found that by removing complex elements, utilizing visualizations, and employing analogies, the scientific content could be made more accessible to high school students. The results of this study suggest that a context-based approach, combined with didactic reduction, can significantly improve students’ understanding and appreciation of chemistry.